HSSEC strategy for decode-and-forward-relaying systems over Nakagami-m fading channels - Swaminathan, Ramabadran (2017)
Distributed switched diversity combining has drawn significant attention in the recent past due to its low-complexity nature in terms of channel state information requirement at the receiving end to achieve full diversity order. In this study, the authors propose a hybrid selection and switch-and-examine combining (HSSEC) scheme, which is a combination of selection combining and SEC schemes, for a multi-relay decode-and-forward system to improve the performance of distributed switched diversity combining schemes proposed in the literature. Furthermore, the performance of HSSEC scheme is investigated over non-identical Nakagami-m fading channels. Average end-to-end symbol error probability (SEP) expression is derived for M-ary phase-shift keying signalling, and in addition asymptotic SEP expression is also derived to analyse diversity order. From the derived asymptotic expression, it is inferred that the HSSEC scheme attains full diversity order over Nakagami-m fading channels, except for the case when threshold signal-to-noise ratio (SNR) is very much lesser than the average SNR. Furthermore, exact outage probability expression is derived for the HSSEC scheme. Finally, in the numerical results, the outage and SEP performances are compared with other schemes proposed in the literature.